PDES-MAS : distributed simulation of multi-agent systems - Suryanarayanan, Vinoth (2014)
Multi-agent systems (MAS) are increasingly being acknowledged as a modelling paradigm for capturing the dynamics of complex systems in a wide range of domains, from system biology to adaptive socio-technical system of systems. The execution of such MAS simulations on parallel machines is a challenging problem due to their dynamic, non-deterministic, data-centric behaviour and nature. These problems are exacerbated as the scale of such MAS models increases. PDES-MAS is a distributed simulation kernel developed specifically to support MAS models addressing the problems of partitioning, load balancing and interest management in an integrated, transparent and adaptive manner. This paper presents an overview of PDES-MAS and for the first time it provides a quantitative evaluation of the system.